Pengaruh Belanja Online Terhadap Kepuasan Konsumen - Nureli Padidah; Dedi Mulyadi (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Everyday life, of course, we see that the use of social media on the internet is growing, not only among adults but also among young people (adolescents). Through social media we can connect with everyone for the need to communicate, increase relationships, add insight and knowledge, education, business, and entertainment. The problem raised in this study is that the existence of Online Shop services (online shopping) can change consumerism among adolescents, such as a high desire for goods to be owned, so students always buy every item sold through the Online Shop (online shopping). for various reasons such as wanting to have unique or more interesting items, items that are rarely used by many people with limited editions (limited edition), or also following current trends to make them look more up-to-date. However, most teenagers forget the main reason why they have to buy these items, resulting in a tendency to buy items that may not be very useful for themselves and only make a waste of themselves without thinking about the benefits of the items they will buy as long as they have satisfied their brand desires